ARsim2care Application User's Manual. - Saraiva, Maria da Conceição Giestas Baía (2020)
ARsim2care allows the integration of Augmented Reality (AR) with Microsoft HoloLens glasses for clinical procedures simulation, such as: Intramuscular injection, Endotracheal Intubation, Nasogastric Tube Insertion and Suctioning via a Tracheostomy Tube. The Application (ARsim2care App) also provides guidance on the previously mentioned procedures. The use of the application is very intuitive.